Disseminação ambiental e prevalência de vírus entéricos em casos de gastroenterite aguda na população infantil da região de São Pedro, Vitória, ES - Pratte-Santos, Rodrigo (2014)
The Vitoria Bay has an extensive mangrove receiving continuous sewage discharge. The local population does use this environment for recreational and fishing purposes. Outbreaks of gastroenteritis have been frequently recorded in this region, possibly due to the lack of hygienic and sanitary behaviors and the close relationship between the population and the contaminated water. Thus, the present study aimed to evaluate the flow of enteric viruses from surface waters of Vitoria Bay to the child population of the region. Samples of surface waters (n=48) were collected from September 2011 to August 2012. Physico-chemical parameters (temperature, pH, salinity, conductivity and turbidity) and microbiological (thermotolerant coliforms, Enterococci and enteric viruses) of water were evaluated. Stool samples from children with gastroenteritis (n=134) were collected from two Health Units, in the same period of water samples collection. The detection of enteric viruses (rotavirus, norovirus GII and adenovirus) was performed by PCR. The viral nucleic acids detected were sequenced for phylogenetic analysis. The physico-chemical analysis of the water indicated that the dissolved oxygen measurements were in disagreement with the CONAMA Resolution n ° 357, 2005. The data of the microbiological analysis of the water showed average concentrations of Enterococci and thermotolerant coliforms ranging from 1.9 x 101 to 3.9 x 103 CFU 100 mL-1 and 1.2 x 102 to 6.5 x 103 CFU 100 mL-1 , respectively. The three enteric viruses were detected in almost all the monitoring period (34/48, 70.8%). The average concentration these viruses in the water ranged from 1.6 x 100 - 1.5 x 104 genomic copies of 100 mL-1 . The close relationship of the population of this region with contaminated water may explain the high prevalence of enteric viruses found in the pediatric population (93.3, 95% CI 87.7 to 96.4). The analysis of viral genomes demonstrated the formation of phylogenetic groups containing enteric viruses detected in water and in the population, indicating a co-circulation of these pathogens in the two matrices. In conclusion, the monitoring provided important data for future studies of public health to reduce morbidity rates and child mortality due to diarrheal diseases.